Congenital Malformations in Sheep - Outbreak Caused by Mimosa tenuiflora - Nogueira, Denise Batista; Ferreira de Souto, Erick Platiní; da Costa Barnabé, Nathanael Natércio; Martins de Oliveira, Artefio; Dantas Medeiros Pereira, Joana Kehrle; Lopes de Lima, André; Nogueira de Galiza, Glauco José; Medeiros Dantas, Antônio Flávio (Acta Scientiae Veterinariae, 2022)
Background: Congenital malformations are anomalies, structural or functional, that occur during the embryonic or fetal phase. There are several causes, one of which is the ingestion of toxic plants. Considering the importance of native toxic plants in the Central Backlands of Ceará state - Brazil, this paper reports cases of congenital malformations in sheep due to ingestion of Mimosa tenuiflora. Cases: Cases of abortion and malformations in sheep, were monitored in a rural property in the municipality of Piquet Carneiro with 20 ruminants (15 sheep and 5 cows) raised on a semi-intensive regime. The animals grazed during the day and were supplemented with corn, having unrestricted access to dam water. On its margins, there was a large amount of jurema preta (Mimosa tenuiflora), which the owner reported that the sheep consumed daily. The owner was unaware of the toxicity of M. tenuiflora but reported that cases of malformations had already occurred on his property some time ago. In an interval of approximately 12 days, 3 sheep miscarriage fetuses with multiple malformations. Malformed fetuses were referred for anatomopathological examination at the Animal Pathology Laboratory of the Veterinary Hospital of Federal University of Campina Grande (UFCG), Campus Patos, Paraíba, Brazil. The fetuses were necropsied and tissue samples of the nervous system and organs from the thoracic and abdominal cavities were collected, fixed in 10% neutral buffered formalin, routinely processed for histopathology, included in paraffin, cut into 3 µm sections and stained with hematoxylin and eosin (HE). At necropsies were observed permanent contracture of the thoracic limb joints (arthrogryposis), particularly at the radio-carpal joints; incomplete medial fusion of the palatal bone, with communication between the oral and nasal cavities (palatoschisis); hypoplasia of the mandibular bone (micrognathia); unilateral hypoplasia of the incisive bone with discontinuity of the upper lip (cheiloschisis); unilateral hypoplasia of the eyeball (microphthalmia); lateral curvature of the cervical spine (scoliosis); and chest deformity characterized by ventral protrusion of the sternum and ribs (Pectus carinatum). At the histopathological evaluation of the tissues, no alterations were observed. Discussion: The diagnosis was based on the epidemiological, clinical, and anatomopathological findings. The semi-intensive management system applied on the property predisposed the sheep to ingestion of M. tenuiflora, which grows abundantly on the property and throughout the Central Backlands of Ceará, Brazil, with a high rate of geographical coverage. Despite that, most rural producers, especially subsistence farmers, are unaware of the toxic and teratogenic properties of the plant. In the northeastern, where there are long periods of drought coupled with forage shortages, poisoning by M. tenuiflora is a common cause of malformation and mortality in lambs. Therefore, it is necessary to adopt preventive measures in herds, such as raising awareness among producers about the toxic potential of some native plants and the practice of producing and supplying silage to animals, so that native toxic plants are not the only food source during the scarcity period. Keywords: arthrogryposis, jurema preta, anomalies, cleft lip, toxic plants. Título: Malformações congênitas em ovinos - surto causado por Mimosa tenuiflora Descritores: artrogripose, jurema preta, anomalias, lábio leporino, plantas tóxicas.